Synthesis of BODIPY FL-tethered ridaifen-B, RID-B-BODIPY, and its localization in cancer cells - Murata, Takatsugu; Komukai, Kyoka; Semba, Yuta; Murata, Eri; Sato, Fumi; Takano, Tomohiro; Tsuchiya, Kaho; Matsuda, Chihiro; Sakai, Anju; Yoneoka, Amane; Takahashi, Shunsuke; Nagahara, Yukitoshi; et al. (Frontiers in Chemistry, 2024)
We synthesized Ridaifen-B Boron dipyrromethene (RID-B-BODIPY) using 2-methyl-6-nitro benzoic anhydride (MNBA)-mediated dehydration condensation reaction between amino alkyltethered RID and BODIPY FL. Comparative experiments between dicyclohexylcarbodiimide (DCC) and MNBA for their coupling reactions demonstrated that MNBA is an effective condensation reagent for amines and BODIPY FL. A cell staining study with RID-B-BODIPY showed intracellular localization of BODIPY FL fluorescence, attributed to the RID-B structure, indicating the successful development of a tool for analyzing intracellular molecular behavior efficiently.